OPTIMALISASI SUMBERDAYA DALAM RANGKA PENINGKATAN PELAYANAN BIDANG PERTANAHAN DI KANTOR KECAMATAN BONTANG BARAT KOTA BONTANG - Arif Pambudi; Aji Ratna Kusuma; Anthonius Margono (Jurnal Administrative Reform, 2017)
The purpose of this study was to analyze the optimization of resources in order to improve the service area of land in the West Bontang District Office as well as revealing the factors supporting and hindering it. This study is descriptive with qualitative approach. Data was obtained by interviews, observation and documents, then the data were analyzed using an interactive model. The results of this study revealed that the optimization of resources in the service area of land on aspects of human resources include employee competence and motivation of employees, and non-human resources includes working procedures and working facilities at the District Office West Bontang been made, but not optimal.